TINDAK TUTUR ILOKUSI DALAM ACARA TALKSHOW HITAM PUTIH TRANS7 - Suryanti Fajria Namsa; Sulastriningsih Djumingin; Muhammad Saleh (Titik Dua: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Illocutionary Speech Acts in Trans7 Black and White Talkshow Events. This research is aimed at identifying and describing illocutionary speech acts contained in the trans7 black and white talkshow. This type of research is a qualitative descriptive study. Data collection techniques used are documentation, observation, and recording techniques. Researcher’s data analysis technique is reducing data by classifying data based on problems, describing narrative, making conclusions, and describing the situation in the talkcshow until the data collection ends. The research results are as follows. The illocutionary speech acts that were found consecutively were assertive illocutionary speech acts with categories (stating, informing, concluding, affirming, informing, boasting, to brag, acknowledging, and complaining); directive by category (advise and ask); commissive by category (offers and promises); and expressive by category (thanking, mocking, greeting, joking, and apologizing). While the form of declarative illocutinary speech acts found only in the first video, namely in the category of dismissing. This is because in the black and white trans7 talkshow there were no speakers who took declarative actions such as imposing a sentence, giving names, baptizing, and resigning from the dsicusison.